The Implementation of The JKN Mobile Application as an Effort to Improve the Quality of Health Services in Indonesia: Literature Review - Nabilah, Hanifah; Permatasari, Putri; Vi'aqila El-Tsana, Ashfiya; Puanurani Anggitya Abdillah, Ratu; Rohadatul 'Aisy, Afifah (LPPM Universitas Prima Nusantara Bukittinggi, 2024)
Background : Management Information System (MIS) plays a crucial role in developing and improving the quality of health services. The Mobile JKN application is one example of the development of information systems and a form of digital transformation in the health sector. Purpose : The purpose of this study is to understand the extent to which the Mobile JKN application has succeeded in improving access to health services for the community and identify inhibiting factors in its use. Methods : This study used Literature Review design. Articles were searched from Google Scholar, PubMed and Science Direct using relevant keywords, then selected according to the criteria and objectives of the study. Results : The results showed that the use of the Mobile JKN application contributed positively to improving service quality. Conclusion : The conclusion of this study is that although there are still some obstacles, the Mobile JKN application is proven to be effective in increasing public satisfaction with health services, as well as helping to overcome the deficit of health workers and infrastructure.